Aviator Carl B. Eielson with a group of men on docks, Seattle, 1929 - Staff Photographer Seattle Post-Intelligencer
Carl Ben Eielson, originally from North Dakota, received pilot training through his service with the Army and later became known as "The Father of Alaskan Aviation." Abandoning flying for law school on the advice of his father, he made an Alaskan acquaintance and soon realized the possibilities that aviation could have in that remote state. He purchased a plane and began flying passengers and supplies before establishing the first airmail route in 1924. From 1926 to 1928, Eielson and George Wilkins attempted three times to fly across the arctic from Point Barrow, Alaska to Svalbard (Spitzbergen), Norway. The successful third attempt in 1928 was the first transarctic flight. Eielson was killed in November 1929 during a rescue attempt in the Bering Strait when his plane crashed in Siberia. This photograph from 1929 of Eielson (in the center with the lighter-colored coat) posing with a group of men on the Seattle docks is from the last year of his life. It has been speculated that it could have been prior to the rescue expedition in which he lost his life. Handwritten on image: [Eielson relief expedition?]. A Fabulous Kingdom: The Exploration of the Arctic; State of North Dakota, Office of the Governor, May 14, 1994 article in the Grand Forks Herald. Date photograph was filed at the Seattle Post-Intelligencer (date of photograph and file date may differ by a month or more): February 23, 1930. 1 glass negative: b&w; 4 x 5 in.